2019
DOI: 10.24843/jbiounud.2019.v23.i02.p01
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi dan frekuensi gen buta warna siswa sekolah dasar di Kabupaten Badung, Bali, Indonesia

Abstract: Buta warna merupakan penyakit keturunan yang terpaut kromosom-X. Buta warna terdiri atas tiga tipe yaitumonokromat (buta warna total), dikromat (buta warna parsial), dan anomali trikromat. Sebagian besar cacatbuta warna tidak terdeteksi, sehingga perlu dilakukan identifikasi sejak dini. Tujuan dari penelitian iniadalah untuk mengetahui prevalensi dan frekuensi gen buta warna pada populasi siswa SD di KabupatenBadung. Kabupaten Badung merupakan salah satu kabupaten di Bali yang terdiri atas enam kecamatan yaitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The color-blind allele frequency of male and female were respctively were 0.048 and 0.008. This allele frequency of color blind is lower than the children of North India is 0.065 (Fareed et al, 2015), elementary students of Kaliwates subdistrict Jember is 0.13 (Ningrum, 2008), and elementary student of Badung regency Bali is 0.0378 (Karolina et al, 2019). The men allele frequency of color blind was higher than female.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The color-blind allele frequency of male and female were respctively were 0.048 and 0.008. This allele frequency of color blind is lower than the children of North India is 0.065 (Fareed et al, 2015), elementary students of Kaliwates subdistrict Jember is 0.13 (Ningrum, 2008), and elementary student of Badung regency Bali is 0.0378 (Karolina et al, 2019). The men allele frequency of color blind was higher than female.…”
Section: Resultsmentioning
confidence: 79%
“…There are prevalence variations in red-green color blindness by population, race, tribe and ethnic (Karolina et al, 2019). The data showed that the number of male color-blind people is more than female color blind so that it can prove that color blindness is a disorder caused by the recessive gene c is linkage on X-chromosome (Nazeer et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Buta warna yang lebih sering ditemukan adalah buta warna partial merah hijau dibandingkan dengan buta warna total [9]. Terdapat variasi prevalensi buta warna merah-hijau (red-green colour blindness) pada ras, suku, dan kelompok etnis [10]. Prevalensi buta warna pada umumnya pada laki-laki lebih tinggi dibandingkan dengan perempuan, pada pia 8% dan perempuan 0,4% [11].…”
Section: Oktarianti Et Al Prevalence Of Phenylthiocarbamide (Ptc) …unclassified